Effects of Pharmacogenetic Screening for CYP2D6 Among Elderly Starting Therapy With Nortriptyline or Venlafaxine: A Pragmatic Randomized Controlled Trial (CYSCE Trial). Issue 6 (November 2019) - van der Schans, Jurjen; Hak, Eelko; Postma, Maarten; Breuning, Laura; Brouwers, Jacobus R.B.J.; Ditters, Kaspar; Jansen, Paul A.F.; Kok, Rob M.; Maring, Jan G.; van Marum, Rob; Mulder, Hans; Nanninga, Jaap; et al.
Abstract: Purpose/Background: The duration of untreated depression is a predictor for poor future prognosis, making rapid dose finding essential. Genetic variation of the CYP2D6 isoenzyme can influence the optimal dosage needed for individual patients. The aim of this study was to determine the effectiveness of CYP2D6 pharmacogenetic screening to accelerate drug dosing in older patients with depression initiating nortriptyline or venlafaxine. Methods/Procedures: In this randomized controlled trial, patients were randomly allocated to one of the study arms. In the intervention arm (DG-I), the specific genotype accompanied by a standardized dosing recommendation based on the patients' genotype and the prescribed drug was directly communicated to the physician of the participant. In both the deviating genotype control arm (DG-C) and the nonrandomized control arm, the physician of the participants was not informed about the genotype and the associated dosing advise. The primary outcome was the time needed to reach adequate drug levels: (1) blood levels within the therapeutic range and (2) no dose adjustments within the previous 3 weeks. Findings/Results: No significant difference was observed in mean time to reach adequate dose or time to adequate dose between DG-I and DG-C. Compared with the nonrandomized control arm group, adequate drug levels were reached significantly faster in the DG-I group (log-rank test; P = 0.004), and there was a similar nonsignificant trend for the DG-C group (log-rank test; P = 0.087). Implications/Conclusions: The results of this study do not support pharmacogenetic CYP2D6 screening to accelerate dose adjustment for nortriptyline and venlafaxine in older patients with depression. Abstract : Supplemental digital content is available in the text.